2014
DOI: 10.1089/ten.tea.2013.0705
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Hybrid Electrospun Nanofiber Layer with Extracellular Matrix Derived from Human Pluripotent Stem Cells, for Regenerative Medicine Applications

Abstract: Extracellular matrix (ECM) has been utilized as a biological scaffold for tissue engineering applications in a variety of body systems, due to its bioactivity and biocompatibility. In the current study we developed a modified protocol for the efficient and reproducible derivation of mesenchymal progenitor cells (MPCs) from human embryonic stem cells as well as human induced pluripotent stem cells (hiPSCs) originating from hair follicle keratinocytes (HFKTs). ECM was produced from these MPCs and characterized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…By decellularizing the composite after a fixed time, the result is self‐termed an available “off‐the‐shelf” implantable product. This composite demonstrated biodegradability and biocompatibility in a rat subcutaneous model, and supported advanced cellular infiltration and habitation compared to uncoated PCL/PLGA scaffolds . Along similar lines, another study utilized a Vicryl knitted mesh made of polyglactin 910 (a 90:10 copolymer of glycolic acid and lactic acid (PLGA)), and cultured either mesenchymal stem cells, normal human articular chondrocytes, or normal human dermal fibroblasts onto both sides of the PLGA mesh.…”
Section: Types Of Biohybrid Materialsmentioning
confidence: 82%
See 1 more Smart Citation
“…By decellularizing the composite after a fixed time, the result is self‐termed an available “off‐the‐shelf” implantable product. This composite demonstrated biodegradability and biocompatibility in a rat subcutaneous model, and supported advanced cellular infiltration and habitation compared to uncoated PCL/PLGA scaffolds . Along similar lines, another study utilized a Vicryl knitted mesh made of polyglactin 910 (a 90:10 copolymer of glycolic acid and lactic acid (PLGA)), and cultured either mesenchymal stem cells, normal human articular chondrocytes, or normal human dermal fibroblasts onto both sides of the PLGA mesh.…”
Section: Types Of Biohybrid Materialsmentioning
confidence: 82%
“…Without intervention, ECM‐based materials are most often degraded in vivo, and are associated with constructive tissue remodeling and minimal fibrosis . As of yet, the specific cell signaling events by which ECM biomaterials modulate the host macrophage population toward a more constructive remodeling phenotype are not fully understood . In several examples, the presence of ECM components was shown to influence the initial response of the immune system to prohealing, despite the polymer components that would be expected to individually illicit an inflammatory response .…”
Section: Other Considerations: Inflammatory Responsementioning
confidence: 99%
“…The PLGA nanofibers were also modified with ECM components. In a study by Shtrichman et al [93], the PLGA nanofibrous scaffolds were modified with ECM deposited on these scaffolds by mesenchymal progenitor cells, derived from human embryonic stem cells, and human induced pluripotent stem cells, originating from hair follicle keratinocytes, which were cultured on the scaffolds and removed by subsequent decellularization. Subcutaneous implantation of the ECM-modified scaffolds in rats then showed that this stem cell-derived construct is biocompatible, biodegradable, and holds great potential for tissue regeneration applications.…”
Section: Nanofibers From Synthetic Degradable Polymersmentioning
confidence: 99%
“…This process can be applied as a template for the growth and remodeling of the ECM. [50,51] Interestingly, Zhou et al reported that CDMs promoted peripheral nerve repair when L929 mouse fibroblast cells from adipose tissue were seeded onto ≈10 S cm −1 conductive mats combining electrospun poly(L-lactic acid) (PLLA) fibers and electrochemically deposited polypyrrole (PPy) nanoparticles. When rat PC12 cells were seeded onto the combined PLLA/PPy/ECM decellularized scaffolds (containing laminin, fibronectin, and collagen), their neurites were seen to differentiate and protrude.…”
Section: Electrospinningmentioning
confidence: 99%